Pencirian minyak mentah berlilin melalui kajian fizikal dan hubungannya dengan masalah parafin - Abd. Kadir, Abd. Aziz; Hassan, Zulkafli (Penerbit UTM Press, 1991)
Solid deposition, generically known as paraffin deposition is a problem which occurs during oil production, especially for wells which are producing waxy crude. High operating cost is incurred every year to control and manage paraffin problem. Techniques for the prevention and treatment of deposition will depend on factors which influence the deposition process itself. A good understanding of the waxy crude characteristics can help in the prediction, treatment and designing suitable production systems in order to manage the problem effectively. This report discusses the results obtained from the laboratory study on waxy crude characteristic. Four crude samples from the Malaysian oilfields were analysed.